Monitoring Receptor-Ligand Interactions between Surfaces by Thermal Fluctuations - Chen, Wei (The Biophysical Society, 2008)
We describe a new method for determining receptor-ligand association/dissociation events across the interface of two surfaces (two-dimensional binding) by monitoring abrupt decrease/resumption in thermal fluctuations of a biomembrane force probe. Our method has been validated by rigorous control experiments and kinetic experiments. We show that cellular on-rate of association can be measured by analysis of intervals from a dissociation event to the next association event (waiting times). Similarly, off-rate of molecular dissociation can be measured by analysis of intervals from an association event to the next dissociation event (bond lifetimes). Different types of molecular bonds could be distinguished by different levels of reduction in thermal fluctuations. This novel method provides a powerful tool to study cell adhesion and signaling mediated by single or multiple receptor-ligand species.